An efficiency analysis of the Malaysian economic sectors: Policy or institution implications - ERIC BALAN; MOHAMMAD SAEED (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: The study aims to analyze the economic efficacy of different industries that produce a country’s GDP. These industries were also studied because of their significant economic impact on the country. Methodology: The research utilized Data Envelopment Analysis to compare and contrast two strategies for gauging the efficacy of administrative and planning processes: the CCR and the BCC. The analysis revealed problems and implications for policy and institutions in the Malaysian economy. Findings: The analysis conclusively established this when it revealed the sectors were providing insufficient outputs to the national economy. These industries are crucial to the country’s output. Still, they are also affected by external factors such as those occurring in the rest of the world, and the current development crisis in Malaysia has only worsened the situation. The focus then shifts to economic policies and institutions’ ability to withstand outside interferences. Implications/Novel Contribution: The study’s rejection of the null hypothesis raised questions about the sectors’ respective allocations of resources. Allocations had remained flat over the 20 years from 2000-2019, resulting in inefficiencies in policy implementation and the inability of institutions to fulfill their intended function. The study brings policy insights for policy makers working in economic development sector.